Self-reported health problems and sickness absence in different age groups predominantly engaged in physical work. Issue 11 (15th February 2007) - Taimela, Simo; Lr, Esa; Malmivaara, Antti; Tiekso, Jaakko; Sintonen, Harri; Justn, Selina; Aro, Timo
Abstract : Objectives: To study the associations between self-reported health problems and sickness absence from work. Methods: The results of a questionnaire survey were combined with archival data of sickness absence of 1341 employees 88 males; 62 blue-collar in the construction, service and maintenance work within one corporation in Finland. Sex, age and occupational grading were controlled as confounders. A zero-inflated negative binomial ZINB regression model was used in the statistical analysis of sickness absence data. Results: The prevalence of self-reported health problems increased with age, from 23 in 1830-year-olds to 54 in 5561-year-olds. However, in those aged 1830 years, 71 had been absent from work and in those aged 5561 years this proportion was 53. When health problems and occupational grading were accounted for in the ZINB model, age as such was not associated with the number of days on sick leave, but the young workers still had higher propensity for any sickness absence than the old. Self-rated future working ability and musculoskeletal impairment were strong determinants of sickness absence. Among those susceptible to taking sick leave, the estimated mean number of absence days increased by 14 for each rise of 1 unit of the impairment score scale 010. Conclusions: Young subjects had surprisingly high probability for sickness absence although they reported better health than their older colleagues. A higher total count of absence days was found among subjects reporting health problems and poorer working ability, regardless of age, sex and occupational grade. These findings have implications for both management and the healthcare system in the prevention of work disability.